Investigation and management of an outbreak of COVID-19 infection in an acute admission unit in a District General Hospital: lessons learnt - Chiranthi Iresha Kannangara; Prema Seetulsingh; Jiovanna Foley; Glynis Bennett; Tracey Carter (Elsevier, 2021)
Summary: Background: SARS-CoV-2 outbreaks are difficult to recognise and control due to its high infectivity and the wide range of clinical manifestations of the infection. An outbreak at Watford general hospital provided an opportunity to recognise the complexity involved in a COVID-19 outbreak investigation. Methods: An outbreak control team (OCT) was convened. The terms outbreak, a case and a significant exposure were defined as per Public Health England (PHE) Guidance and in the context of the local outbreak. Root cause analyses (RCAs) were carried out on cases to identify possible causes, possible route of transmission and any learning points. All contact patients and staff were screened with RT PCR and genomic sequencing was performed on a set of positive specimens.In addition to active contact tracing, screening and cohorting of patients and staff, standard and transmission-based precautions were reinforced to control the outbreak. Findings: Fifteen patients and four staff members were identified in this outbreak investigation. With contact tracing, screening and through strict infection control measures the outbreak was brought under control. Conclusion: We could successfully contain the spread of this outbreak following PHE outbreak control guidelines and our local guidelines. We recognised several challenges in investigating a COVID-19 outbreak in a hospital setting. Problems arising from variable sensitivity of the tests, difficulty in differentiating COVID-19 related symptoms from underlying diseases, problems related to establishing the route of transmission, issues with contact tracing are discussed. Additionally, the importance and limitations of genomic studies in COVID-19 are discussed.